If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2y + -3z = 9 Solving x + 2y + -3z = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y + -3z = 9 + -2y Combine like terms: 2y + -2y = 0 x + 0 + -3z = 9 + -2y x + -3z = 9 + -2y Add '3z' to each side of the equation. x + -3z + 3z = 9 + -2y + 3z Combine like terms: -3z + 3z = 0 x + 0 = 9 + -2y + 3z x = 9 + -2y + 3z Simplifying x = 9 + -2y + 3z
| X+24+2x=-19-2x-22 | | -9w=-12 | | -2a+8+6a=9a-3a | | 5a=-2 | | 18x^3-27x= | | 52+5y-21=17y-14-3y | | 3x+4/2x+3=x+14/x+8 | | 20=-6a | | x+3/x+1=x-3/x-8 | | -7r=6 | | 4z-15-z+3=0 | | 62-5x=10x+18 | | -6x=9 | | 4d=8-4d | | 4r=-4 | | 9/x+5=15/x+3 | | -(5a+8)+2(a+7)=-4a-5a | | (5x+1)3=15x+3 | | 6x+8/x-2=8 | | m,7-25=-19 | | 3i+3=10-4i | | 4x+4/2=6 | | 2a^2+12a=0 | | 4x+59=10+11 | | 4f=12 | | 20=5a | | 5x(5x-7)(9x+5)=0 | | 3x-9/3=8 | | -8=2b | | -33=-11t | | 4=-2u | | -5+1/2x=-4 |